(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the theoretical and methodological foundations of the development of hygienic competence in students of medical educational institutions, the pedagogical mechanisms and technological foundations of development. Also, the pedagogical necessity of developing hygienic competence among students of medical educational institutions was analyzed.